Effects of fixed orthodontic lingual retainers on PDL stress, root resorption risk, and tooth displacement - Mehrnaz Moradinejad; Marzieh Mazhari; Mohsen Mazhary; Alireza Hashemi Ashtiani; Marzie Yazdi; Vahid Rakhshan (Scientific Reports)
Abstract To date, no study has compared the effects of CAD/CAM versus flexible multistrand wire (FMS) retainers in the presence/absence of root resorption and/or alveolar crestal bone resorption on the anterior mandibular teeth’s stresses/displacements. Therefore, this simulation was conducted. Developed were 8 mandible models with six anterior teeth. Models 1 to 4 had FMS retainers; models 5 to 8 had nickel-titanium CAD/CAM retainers. Models #1 and 5: Both bone and roots were intact; #2 and 6: Only alveolar crests had resorption (2 mm); Models #3 and 7: Only roots had resorption (2 mm); Models #4 and 8: Both the bone and roots were resorbed (each 2 mm). Models were loaded with a vertical force of 187 N. Estimated were their PDL pressures, increased risks of root resorption (defined as PDL stresses > 0.0047 MPa), and 3D tooth movements. Right and left sides were averaged. Scenarios were compared. The present study supports the use of this type of FMS retainer due to less stress, less root resorption risk, and smaller displacements where both root and alveolar crest resorption exist. In terms of PDL stress and root resorption risk of the six anterior teeth, CAD/CAM retainers might act similar to or worse than conventional multistrand retainers (except for lateral incisors in models with crestal bone resorption). CAD/CAM retainers in cases with both crestal and root resorptions might pose a considerably high risk of additional root resorption. For canines and central incisors, the presence of root resorption versus bone resorption might not matter much for increasing their PDL stresses. Nevertheless, for lateral incisors, bone resorption may affect their PDL stresses more than root resorption. FMS might be superior to CAD/CAM in most evaluated scenarios, except few scenarios like intact bone and roots.